Pacific Island Countries : In Search of a Trade Strategy - Chen, Hong (IMF Working Papers; Working Paper, 2014)
International trade is vital for economic prosperity in Pacific island countries, but their trade performance has been weak over the past decade with the exception of resource-rich countries. Small country size and remoteness from global economic centers may have contributed to this relatively poor performance. However, the emergence of Asia as a global economic center presents Pacific island countries with an unprecedented opportunity to develop trade with Asia, particularly in tourism for a number of PICs. Moreover, if a strong two-way linkage is established between tourism and agriculture, Pacific island countries stands a better chance to improve broad-based growth.